Autoeficácia, apoio social, percepção do ambiente e atividade física de adolescentes: uma análise longitudinal - Cabral, Luciana Gatto de Azevedo (2020)
The aim of this study was to analyze longitudinal associations of self-efficacy, social support and the environment with physical activity of adolescents from João Pessoa (PB) and to verify moderating effect of sex and age on its associations. This is a longitudinal observational study and will analyze data from the “Longitudinal Study on Sedentary Behavior, Eating Habits, Physical Activity and Adolescent Health” - LONCAAFS. The sample was composed of adolescents from 10 to 14 years of age, of both sexes, enrolled in the sixth year of elementary school in the municipal and state schools of the city of João Pessoa (PB) in 2014 and who were followed up in 2015, 2016 and 2017. Data collection was carried out at school during regular class hours. A face-to-face questionnaire and anthropometric measures (weight and height) was conducted by a trained team following a standardized protocol. The following variables were considered for characterization of the sample and adjustments: sex, age, skin color, economic class, length of residence in the neighborhood and nutritional status. The variables self-efficacy, social support and environment were measured using scales of 4, 15 and 15 items, respectively. Physical activity was measured using the QAFA questionnaire - Physical Activity Questionnaire for Adolescents. Data were entered twice in EpiData 3.1 and checked for consistency and amplitude. Generalized Estimation Equations were used to compare the mean scores of each of the variables over the four years of the study and to test the associations (individually and synergistically) between self-efficacy, social support from father, mother and friends, the perception of the environment and physical activity of adolescents. The average scores for self-efficacy (β = 0.005; p <0.001), perception of availability of places to practice (β = 0.138; p <0.001), traffic safety (β = 0.103; p <0.001) and safety (β = 0.161; p <0.001) showed a linear upward trend. The average scores of social support from father (β = -0.548; p <0.001), mother (β = -0.513; p <0.001), friends (β = -0.282; p <0.001) and the practice of physical activities (β = -60.3; p <0.001) showed a decline. Social support was positively associated with the physical activity of adolescents both individually (father β = 24.88; p <0.001, mother β = 21.63; p <0.001 and friends β = 20.41; p <0.001), and synergistically (β = 36.17; p <0.001). Self-efficacy was negatively associated (β = -34.16; p <0.001) and the items of perception of the environment were not associated with the physical activity of the adolescents individually. Individually, the items of perception of the environment were not associated with the physical activity of the adolescents, but when combined, a negative association was found (β = -3.68; p <0.001). The global score of self-efficacy, social support and perception of the environment was positively associated with the physical activity of adolescents (β = 161.56; p <0.001).